2012
DOI: 10.1080/08959420.2012.676315
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Home Care to Nursing Home: Unmet Needs in a Home- and Community-Based Program for Older Adults

Abstract: A major effort is under way nationally to shift long-term care services from institutional to home- and community-based settings. This article employs quantitative and qualitative methods to identify unmet needs of consumers who transition from a statewide home- and community-based service program for older adults to long-term nursing home residence. Administrative data, care manager notes, and focus group discussions identified program service gaps that inadequately accommodated acute health problems, mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 27 publications
3
43
0
2
Order By: Relevance
“…A study identified unmet needs of individuals who transitioned from Connecticut's HCBS program to NHs using administrative data, care manager notes, and focus groups (Robison, Shugrue, Porter, Fortinsky, & Curry, 2012). Study findings indicated that acute health problems, mental health issues, and family caregiver stress were inadequately addressed.…”
Section: Supporting Transitions Between Nursing Home and Community Sementioning
confidence: 99%
“…A study identified unmet needs of individuals who transitioned from Connecticut's HCBS program to NHs using administrative data, care manager notes, and focus groups (Robison, Shugrue, Porter, Fortinsky, & Curry, 2012). Study findings indicated that acute health problems, mental health issues, and family caregiver stress were inadequately addressed.…”
Section: Supporting Transitions Between Nursing Home and Community Sementioning
confidence: 99%
“…1 Between 2000 and 2013, in Organisation for Economic Co-operation and Development (OECD) countries, the average proportion of older care-dependent people receiving long-term care increased from 1.9% to 2.3%. By 2050, the percentage of the population older than 80 is expected to have risen from 4% to 10%, linked to a projected increase in the prevalence of people living with dementia from 14.5 to 22.5 per 1000 population by 2035.…”
mentioning
confidence: 99%
“…In addition, home- and community-based program services’ unmet needs highlighted an inadequate workforce, transportation barriers, and limited supportive housing options [26]. Therefore, the aim of this study was to evaluate the performance of Korean community-based home healthcare project for older adults.…”
Section: Introductionmentioning
confidence: 99%